CD5L attenuates allergic airway inflammation by expanding CD11chigh alveolar macrophages and inhibiting NLRP3 inflammasome activation via HDAC2. Issue 3 (26th July 2022) - Weng, Danlin; Gao, Song; Shen, Hailan; Yao, Shifei; Huang, Qi; Zhang, Yanyu; Huang, Wenjie; Wang, Yan; Zhang, Xuemei; Yin, Yibing; Xu, Wenchun
Abstract: Allergic asthma is an airway inflammatory disease dominated by type 2 immune responses and there is currently no curative therapy for asthma. CD5‐like antigen (CD5L) has been known to be involved in a variety of inflammatory diseases. However, the role of CD5L in allergic asthma remains unclear. In the present study, mice were treated with recombinant CD5L (rCD5L) during house dust mite (HDM) and ovalbumin (OVA) challenge to determine the role of CD5L in allergic asthma, and the underlying mechanism was further explored. Compared with PBS group, serum CD5L levels of asthmatic mice were significantly decreased, and the levels of CD5L in lung tissues and bronchoalveolar lavage fluid (BALF) were significantly increased. CD5L reduced airway inflammation and Th2 immune responses in asthmatic mice. CD5L exerted its anti‐inflammatory function by increasing CD11c high alveolar macrophages (CD11c high AMs), and the anti‐inflammatory role of CD11c high AMs in allergic asthma was confirmed by CD11c high AMs depletion and transfer assays. In addition, CD5L increased the CD5L + macrophages and inhibited NLRP3 inflammasome activation by increasing HDAC2 expression in lung tissues of asthmatic mice. Hence, our study implicates that CD5L has potential usefulness for asthma treatment. Abstract : Administration of exogenous CD5L attenuates allergic airway inflammation and type 2 immune responses by expanding CD11c high AMs in mice. Besides, CD5L inhibited NLRP3 inflammasome activation in allergic asthma mice by increasing HDAC2 expression. The arrows do not represent direct or indirect effects, and they just mean that there is a regulatory relationship between cells or molecules.